Transforming assessment in higher education with Canva for creative and visual learning - Syed Abdullah, Sharifah Sarimah; Omar, Mawardi; Ahmad Shukri, Fuziatul Norsyiha; Mohd Rosly, Wan Nur Shaziayani (Unit Penerbitan JSKM, 2025)
Canva is a cutting-edge technology for developing evaluations in higher education, and this study investigates its application. Traditional assessments often rely on text-based formats that may not effectively engage all learners or support the development of essential 21st-century skills. Canva provides a creative and user-friendly platform that allows educators to design visually appealing, interactive, and student-centered assessments such as infographics, digital journals, and collaborative presentations. Its features, including real-time collaboration, artificial intelligence tools, and integration with learning management systems, help enhance student engagement, support various learning styles, and encourage critical thinking and creativity. Based on constructivist and social learning theories, the study highlights how Canva fosters deeper understanding and promotes teamwork among students. It also emphasizes the platform’s usefulness in both online and blended learning environments, offering flexible and inclusive assessment approaches. The findings suggest that Canva can improve traditional assessment practices by making them more meaningful, accessible, and aligned with the needs of modern education.